A taxonomy of intrusion response systems. (1st February 2007) - Stakhanova, Natalia; Basu, Samik; Wong, Johnny
Recent advances in the field of intrusion detection brought new requirements to intrusion prevention and response. Traditionally, the response to an attack is manually triggered by an administrator. However, increased complexity and speed of the attack-spread during recent years show acute necessity for complex dynamic response mechanisms. Although intrusion detection systems are being actively developed, research efforts in intrusion response are still isolated. In this work we present a taxonomy of intrusion response systems, together with a review of current trends in intrusion response research. We also provide a set of essential features as a requirement for an ideal intrusion response system.